Constructions and technological aspects of furniture panels in regulatory documents - Podibka, T.I. (Forestry, Forest, Paper and Woodworking Industry, 2018)
A detailed analysis of regulatory documents for furniture panels was made. The regulatory framework for furniture panels was analyzed, in particular the following documents: DSTU EN 12775:2004. Wooden shields. Classification and terminology (EN 12775:2001, IDT), DSTU EN 13017-1:2004, DSTU EN 13017-2:2004, DSTU EN 13354:2009, DSTU EN 14080:2013. It was found that the quality of furniture boards is determined according to DIN EN 13017-1:2000 (DSTU EN 13017-1:2004 – for softwoods) and DIN EN 13017-2:2000 (DSTU EN 13017-2:2004 – for hardwoods ). Furniture boards made of softwood are divided into 5 classes of surface quality (0, A, B, C, S), hardwood - into 3 classes (A, B, C). Quality is determined by the best side, and when marking, two sides are indicated - front and back (for example, A/B). It was determined that the most common defects that affect the quality of furniture boards are knots, cracks, skewness and others that are classified according to DSTU 2152-93 and measured according to EN 1310:1997 (DSTU EN1310:2005). The spheres of use of furniture boards are established, which are classified according to EN 13353:2008 into 3 classes: SWP1 (in dry conditions): SWP2 (in wet conditions): SWP3 (in atmospheric conditions). The main types of furniture panel designs produced by domestic and European enterprises are analyzed. It has been established that on the market of Ukraine, the most common recommendations for the manufacture of a furniture panel are the following species: oak, beech, ash and pine with the following most typical dimensions for the dimensions of this panel material: thickness 18, 20, 28, 30 and 40 mm, width - 300 , 600, 900 and 1200 mm and 1000, 2000, 3000, 4000 and 5000 mm long. It is planned to carry out a more in-depth analysis of the study of the change in shape of single-layer wooden shields of 5 thicknesses (18, 23, 30, 37 and 42 mm) with the widths of sections of lamellas of 20, 32, 50, 68 and 80 mm, and the lengths of these sections — 150, 322, 575, 828 and 1000 (solid-lamella shield) mm, when they are affected by temperature and humidity factors.